Pengaruh Ulasan Produk, Kemudahan Navigasi, dan Harga Terhadap Keputusan Pembelian pada Tokopedia - Yasin, Muhammad; Tanuwijaya, Haryanto; Suhandiah, Sri (Jurnal Manajemen dan Organisasi, 2025)
Technological advancements have progressed at an extraordinary pace, profoundly impacting various sectors, including e-commerce. This study investigates the influence of product reviews, ease of navigation, and pricing on purchasing decisions among Tokopedia users. A quantitative research method was employed, utilizing a structured questionnaire to gather responses. Data were analyzed using SmartPLS version 4, with evaluations covering both the inner and outer models. The inner model assessment included path coefficients, Cronbach’s alpha, and R-squared values, while the outer model focused on convergent validity, discriminant validity, and composite reliability. The results show that product reviews have a significant positive effect on purchasing decisions (t-value = 3.589 > 1.96; p = 0.000 < 0.05), supporting hypothesis H1. Ease of navigation also has a significant positive influence (t-value = 5.009 > 1.96; p = 0.000 < 0.05), confirming hypothesis H2. Furthermore, pricing was found to significantly affect purchasing decisions (t-value = 2.676 > 1.96; p = 0.007 < 0.05), supporting hypothesis H3. The study concludes that product reviews, ease of navigation, and pricing each have a positive and statistically significant impact on purchasing decisions on the Tokopedia platform.